Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 209241 by mr W last updated on 05/Jul/24

Answered by A5T last updated on 05/Jul/24

Commented by A5T last updated on 05/Jul/24

(√(a^2 −6^2 ))+a=18⇒(18−a)^2 =a^2 −36⇒a=10  ⇒[Shaded]=(1/2)×6×a=3a=30

$$\sqrt{{a}^{\mathrm{2}} −\mathrm{6}^{\mathrm{2}} }+{a}=\mathrm{18}\Rightarrow\left(\mathrm{18}−{a}\right)^{\mathrm{2}} ={a}^{\mathrm{2}} −\mathrm{36}\Rightarrow{a}=\mathrm{10} \\ $$$$\Rightarrow\left[{Shaded}\right]=\frac{\mathrm{1}}{\mathrm{2}}×\mathrm{6}×{a}=\mathrm{3}{a}=\mathrm{30} \\ $$

Answered by efronzo1 last updated on 05/Jul/24

Terms of Service

Privacy Policy

Contact: info@tinkutara.com